Tumour microenvironment landscape and immunotherapy response in bladder cancer decoded by stromal MOXD1 based on copper-related genes signature - Wang, Wenhao; Hua, Shan; Li, Jianying; Zhao, Jing; Zhang, Yu; Jiang, Juntao; Han, Bangmin (Frontiers in Oncology, 2022)
Introduction We aimed to develop a copper-related gene (CRG) signature that can be used to evaluate prognosis and guide therapeutic management in bladder cancer patients. Methods The raw transcriptome profiles and clinical data of 405 bladder samples were downloaded from The Cancer Genome Atlas (TCGA) database, and differentially expressed copper-related genes were identifified using the Molecular Signatures Database (MSigDB) database and univariate and multivariate Cox regression analysis. A multigene prognostic signature based on 14 CRGs was developed by least absolute shrinkage and selection operation (LASSO) analysis in the TCGA cohort and validated in the Gene Expression Omnibus (GEO) cohort. Multiple analyses were then conducted in which the nomograms, clinicopathological features, immune-related cell infifiltration characteristics, and therapy responses of the high- and low-risk score groups were compared. Results A 14 CRGs signature was constructed and used to classify patients into high-risk and low-risk groups. Compared to patients classifified as high-risk, low-risk patients in both the TCGA cohort and the GEO cohort had better overall survival. Patients in high-risk groups had more aggressive clinical features, immunologically “cold” infifiltrating characteristics, and experienced lower therapeutic effificacy. We identifified a CRG signature of bladder cancer and validated it using unsupervised clustering analysis. Monooxygenase DBH-like 1 (MOXD1) was further identifified, and its potential for evaluating the tumor immune microenvironment and predicting the immunotherapy response was explored. Discussion These results suggest a novel research direction for precision therapy of bladder cancer and demonstrate that copper-related genes can play a promising role in predicting prognosis and may serve as therapeutic targets for bladder cancer.